SEKOLAH DAN PEMBENTUKAN KARAKTER MORAL : (Studi Implimentasi Pendidikan di Sekolah dan Lingkungan Sosial) - Muammar, Muammar (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2023)
The educational process always takes place in a certain environment, both environments related to space and time. The environment in relation to education is everything that is outside the child in this universe. Educators are part of the environment too, but because the nature of their influence is different from the influence exerted by other environments, educators are separated from the environment. Formation of valuable educationCharacter is defined as the embodiment of character, character, morals inherent in a person's personality which is formed from the results of internalization which is useful as a basis for thinking and behaving. Nuances of character or what is better known as personality emerge and become ingrained in the soul of every human being. Of course, everyone basically has good character and the environment influences it. Character includes all behavior, thought patterns and ways of looking at a person in determining an attitude which includes beliefs, morals and habits. Character is defined as the embodiment of character, character, morals inherent in a person's personality which is formed from the results of internalization which is useful as a basis for good thinking, behavior and morals. Next, the author explains a little about the methodology that the author uses in this paper, namely Research or scientific methods are procedures or steps in obtaining scientific knowledge or knowledge. So research methods are a systematic way to organize knowledge. Meanwhile, research techniques are ways to carry out research methods. Research methods usually refer to forms of research. In this writing, the author uses the Descriptive Method (describing) technique, namely the method used to look for elements, characteristics, properties of a phenomenon.